Tritodynamia bengalensis n. sp., a new species of brachyuran crab from West Bengal state, India (Decapoda: Brachyura: Macrophthalmidae) - Trivedi, Jigneshkumar N.; Mitra, Santanu; Ng, Peter K. L. (Zootaxa, 2021)
Tritodynamia bengalensis n. sp. is described on the basis of a male specimen dredged from the shallow coastal waters of West Bengal state, India. The new species is morphologically similar to T. bidentata Yang & Tang, 2005 and T. serratipes Anker & Ng, 2014, but can be distinguished by the carapace shape, dentition of the pollex, relative length of the dactylus of the third maxilliped, proportions of the propodus of the third pereopod, and structure of the male left gonopod. This is the first record of the genus Tritodynamia from India.